Estimation of Stature & Gender from Thumb Indices in Indian Population - Mohite Hemlata S; Kakade Satish V; Mohite Sandeep S; Roy Priya P; Doshi Megha A (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Human characteristics like stature and gender identification on basis of human remains is a crucial element of any medicolegal investigation and is especially important in the field of forensic anthropometry. Thus, this study was undertaken with the aim of determining stature and gender by using thumb indices in the Indian population.Material & Methods: 568 adults (294 males and 274 females) belonging age between 18-25 years participated in the present study. Thumb length, breadth, thickness and circumference were measured by time to time calibrated measuring tape and digital vernier caliper. Unpaired ‘t’ test, Person Correlation Coefficient, Linear and Logistic regression methods used to analyze the data.Results: This study showed significant correlation of thumb indices with stature & gender.Conclusion: The stature and gender identification models are helpful to forensic experts and crime scene authorities to determine the stature and gender of an isolated thumb.